THE UPLIFT OF ALL (SARVODAYA) THROUGH THE UPLIFT OF THE LAST (ANTYODYA): Gandhian Perspectives toward Knowledge Societies - Nandhikkara, Jose (Journal of Dharma, 2019)
As we celebrate 150th birth anniversary of Mahatma Gandhi, Journal of Dharma (Vol. 44.4) is investigating Gandhian views on Knowledge, Education and Societies. Journal of Dharma also remember with gratitude a Gandhian before Gandhi, St Kuriakose Elias Chavara, the founding inspiration for Journal of Dharma, as we begin his 150th death anniversary. For Gandhi (as well as for Kuriakose Elias), "Education means all-round drawing out of the best in child and man—body, mind, and spirit." Both Kuriakose Elias and Gandhi brought into harmony darsan (vision) and tapas (mission) for sarvodaya (the uplift of all), through antyodya (the uplift of the last), integrating the moral and knowledge, and becoming the change that they wanted to bring into society. They took pioneering steps for universal education for educating the poor and the marginalised, and welfare of the society through the welfare of the poorest. They envisioned that the uplift of the last would certainly result in the uplift of all, and by focussing on the last, the weakest gets priority in the welfare schemes and development plans.